Functional annotation and identification of novel drug targets from uncharacterized proteome of Trichuris trichiura - Kanchan Rauthan; Saranya Joshi; Lokesh Kumar; Sudhir Kumar (Journal of Infection in Developing Countries, 2025)
Introduction: Trichuris trichiura, a soil-transmitted helminth, resides in the large intestine of humans, causing an asymptomatic disease known as trichuriasis. This global health concern is particularly prevalent in low- or middle-income countries, representing a significant burden on public health as one of the most neglected tropical diseases. The diminishing effects of currently available anthelmintic drugs, attributed to escalating drug resistance, warrants an urgent need for alternative and more potent vaccines or drugs. A substantial portion of the proteins in the T. trichiura genome are uncharacterized and their annotation might offer insight into the parasite's invasion, interaction, and survival mechanisms inside the host. Hence, this study is aimed to provide functional annotations for the uncharacterized proteins identified in the proteome of T. trichiura.